Comparative study of trastuzumab modification analysis using mono/multi-epitope affinity technology with LC-QTOF-MS - Chengyi Zuo; Jingwei Zhou; Sumin Bian; Qing Zhang; Yutian Lei; Yuan Shen; Zhiwei Chen; Peijun Ye; Leying Shi; Mao Mu; Jia-Huan Qu; Zhengjin Jiang; et al. (Journal of Pharmaceutical Analysis)
Dynamic tracking analysis of monoclonal antibodies (mAbs) biotransformation in vivo is crucial, as certain modifications could inactivate the protein and reduce drug efficacy. However, a particular challenge (i.e. immune recognition deficiencies) in biotransformation studies may arise when modifications occur at the paratope recognized by the antigen. To address this limitation, a multi-epitope affinity technology utilizing the metal organic framework (MOF)@Au@peptide@aptamer composite material was proposed and developed by simultaneously immobilizing complementarity determining region (CDR) mimotope peptide (HH24) and non-CDR mimotope aptamer (CH1S-6T) onto the surface of MOF@Au nanocomposite. Comparative studies demonstrated that MOF@Au@peptide@aptamer exhibited significantly enhanced enrichment capabilities for trastuzumab variants in comparison to mono-epitope affinity technology. Moreover, the higher deamidation ratio for LC-Asn-30 and isomerization ratio for HC-Asn-55 can only be monitored by the novel bioanalytical platform based on MOF@Au@peptide@aptamer and liquid chromatography-quadrupole time of flight-mass spectrometry (LC-QTOF-MS). Therefore, multi-epitope affinity technology could effectively overcome the biases of traditional affinity materials for key sites modification analysis of mAb. Particularly, the novel bioanalytical platform can be successfully used for the tracking analysis of trastuzumab modifications in different biological fluids. Compared to the spiked phosphate buffer (PB) model, faster modification trends were monitored in the spiked serum and patients' sera due to the catalytic effect of plasma proteins and relevant proteases. Differences in peptide modification levels of trastuzumab in patients' sera were also monitored. In summary, the novel bioanalytical platform based on the multi-epitope affinity technology holds great potentials for in vivo biotransformation analysis of mAb, contributing to improved understanding and paving the way for future research and clinical applications.